Adverse events of herbal decoction: A systematic review and meta-analysis over past 10 years - Han-Gyul Lee; Hyein Jeong; Chan-Young Kwon; Kyeong-Han Kim; Soo Hyun Sung; Ji Eun Han; Minjung Park; Soobin Jang (Elsevier, 2024)
Background: Herbal decoctions (HDs) are the oldest and most common herbal medicine formulations. Different HDs exist, and some consumers are concerned that they may become contaminated during manufacturing. Therefore, the need for a safety assessment of HDs has been raised. This study aimed to investigate the adverse events (AEs) associated with HDs by comprehensively analyzing randomized controlled trials (RCTs) using systematic reviews and meta-analyses. Methods: A systematic search was conducted on PubMed, Embase, and the Cochrane Library for articles published up to November 2022. The included RCTs compared HDs with other treatments published between 2013 and 2022, and the risk of bias was assessed using RevMan 5.4. Meta-analyses of the number of AEs associated with HDs reported in the included RCTs were also performed. Results: The systematic review included 26 RCTs, and the meta-analysis included 17 RCTs that reported AEs. The meta-analysis comparing HDs with active controls showed that both the number of AEs (14 studies; risk ratio (RR)= 0.50 cases, 95 % confidence interval (CI) [0.29, 0.88]; I2 = 42 %) and the number of patients who complained of AEs (seven studies; RR=0.51 patients, 95 % CI [0.28, 0.94]; I2 =9 %) were fewer in the HDs group than in the active control groups. Conclusion: This study showed that HDs are safer than other conventional medications based on the results of qualitative and quantitative syntheses of RCTs.